History and national identity: The role of museum as non-formal educational institution for students in Malaysia - Halamy, Suhaida (2014)
Museum derived from Latin word ‘mouseion’ which denotes a place or temple devoted to the Muses, the very word conveys to the place of learning and study. A museum is a non-profit, permanent institution in the service of society and its development, open to the public, which acquires, conserves, researches, communicates and exhibits the tangible and intangible heritage of humanity and its environment for the purposes of education, study and enjoyment.(ICOM, 2007). In Malaysia, the understanding among community regarding the importance of museums as non-formal learning institutions in the field of education has not been deep enough.Although currently still a lot of perception that museum as a place to store artifacts and ancient history, the museum is primarily a means to expand human culture and civilization.Museum in Malaysia exist since more than a century ago, but public awareness of the role is still shallow. Interest and inclination to visit the museum being eroded because the existence of a theme park that provides entertainment and sheer pleasure. Hence, this competition seems to obscure and deny the role of the museum.This situation contrasts sharply with the approach of western society about the museum where the museum placed in the special category in their countries and becoming exceptionally most effective institutions as a means of dissemination of knowledge.This paper identified and discussed some important issues about the role of museum as non-formal educational institution. Apart from creating awareness on its role, it putting better hope for the museum can be a method or an alternative to increase the interest among students to learn and understand the history.